Organ donation consent after death - Garcia, Valter Duro; Pestana, José Osmar Medina de Abreu; Pêgo-Fernandes, Paulo Manuel (São Paulo Medical Journal, 2025)
Most countries where organ transplants are performed, defined laws exist to address different legal aspects of these procedures, particularly concerning consent for organ donation after death. The authorization for organ removal for transplantation purposes raises controversial debates, considering its profound ethical and moral implications. It examines core societal values and reflects on fundamental rights, such as respect for human dignity, including the right to personality and autonomy of self-determination. Every individual possesses the freedom to decide regarding certain actions concerning their body according to their own conscience. However, these decisions must be made within certain boundaries to uphold fundamental rights. In Brazil, an individual’s autonomy over their own body is included in three articles of the Constitution. Article 1 emphasizes the principle of human dignity; Article 5 outlines the right to life and the right to freedom; and Article 199 addresses the ability to waive parts of the human body.